Notes on Some Nineveh Horse Lists - Fales, Frederick Mario
copies Rm. 949, K. 952 = ADD 988, K. 968 = ADD 989, K. 12045, 83-1-18, 808, K. 1053 = ABL 68 + K. 1533 = ABL 1450; irginu, ḫarbakanu, ḫaršāju, tuanu.